THE ROLE OF ARTIFICIAL INTELLIGENCE IN IMPROVING THE EFFECTIVENESS OF LEARNING - Sari, Sri Yulia; Purnama, Meira Dwi Indah; Triani, Lidya (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The focus of this article is on the implementation of Artificial Intelligence or artificial intelligence in improving learning efficiency. Artificial Intelligence is the process of designing a machine to behave like a human or other term called cognitive tasks, which is how machines can learn automatically from programmed data and information. Artificial Intelligence as an application that also offers a way to invite users to participate who are not found on outdated documents or in an unchanged environment. Artificial Intelligence will make the data a collection of the learning processes already carried out by the user, and then will provide alternatives and ways of solving them and which are learning solutions that suit the needs of the user. Artificial Intelligence has the ability to encourage and accelerate the discovery of new learning boundaries and the creation of innovative technologies in learning, this is expected to increase effectiveness in the learning process.